Left-right asymmetry specification in amphioxus: review and prospects - Soukup, Vladimir (The International journal of developmental biology, 2017)
Extant bilaterally symmetrical animals usually show asymmetry in the arrangement of their inner organs. However, the exaggerated left-right (LR) asymmetry in amphioxus represents a true peculiarity among them. The amphioxus larva shows completely disparate fates of left and right body sides, so that organs associated with pharynx are either positioned exclusively on the left or on the right side. Moreover, segmented paraxial structures such as muscle blocks and their neuronal innervation show offset arrangement between the sides making it difficult to propose any explanation or adaptivity to larval and adult life. First LR asymmetries can be traced back to an early embryonic period when morphological asymmetries are preceded by molecular asymmetries driven by the action of the Nodal signaling pathway. This review sums up recent advances in understanding LR asymmetry specification in amphioxus and proposes upstream events that may regulate asymmetric Nodal signaling. These events include the presence of the vertebrate-like LR organizer and a cilia-driven fluid flow that may be involved in the breaking of bilateral symmetry. The upstream pathways comprising the ion flux, Delta/Notch, Wnt/β-catenin and Wnt/PCP are hypothesized to regulate both formation of the LR organizer and expression of the downstream Nodal signaling pathway genes. These suggestions are in line with what we know from vertebrate and ambulacrarian LR axis specification and are directly testable by experimental manipulations. Thanks to the phylogenetic position of amphioxus, the proposed mechanisms may be helpful in understanding the evolution of LR axis specification across deuterostomes.
Keywords: Body Patterning; Animals; Signal Transduction; obratlovci; zvířata; signální transdukce; vývojová regulace genové exprese; kopinatci; Gene Expression Regulation, Developmental; Evolution, Molecular; molekulární evoluce; Lancelets; Vertebrates; rozvržení tělního plánu